Facility-based delivery in the context of Zimbabwe's HIV epidemic – missed opportunities for improving engagement with care: a community-based serosurvey. Issue 1 (December 2015) - Buzdugan, Raluca; McCoy, Sandra; Webb, Karen; Mushavi, Angela; Mahomva, Agnes; Padian, Nancy; Cowan, Frances
Abstract Background In developing countries, facility-based delivery is recommended for maternal and neonatal health, and for prevention of mother-to-child HIV transmission (PMTCT). However, little is known about whether or not learning one's HIV status affects one's decision to deliver in a health facility. We examined this association in Zimbabwe. Methods We analyzed data from a 2012 cross-sectional community-based serosurvey conducted to evaluate Zimbabwe's accelerated national PMTCT program. Eligible women (≥16 years old and mothers of infants born 9–18 months before the survey) were randomly sampled from the catchment areas of 157 health facilities in five of ten provinces. Participants were interviewed about where they delivered and provided blood samples for HIV testing. Results Overall 8796 (77 %) mothers reported facility-based delivery; uptake varied by community (30–100 %). The likelihood of facility-based delivery was not associated with maternal HIV status. Women who self-reported being HIV-positive before delivery were as likely to deliver in a health facility as women who were HIV-negative, irrespective of when they learned their status - before (adjusted prevalence ratio (PRa ) = 1.04, 95 % confidence interval (CI) = 1.00–1.09) or during pregnancy (PRa = 1.05, 95 % CI = 1.01–1.09). Mothers who had not accessed antenatal care or tested for HIV were most likely to deliver outside a health facility (69 %). Overall, however 77 % of home deliveries occurred among women who had accessed antenatal care and were HIV-tested. Conclusions Uptake of facility-based delivery was similar among HIV-infected and HIV-uninfected mothers, which was somewhat unexpected given the substantial technical and financial investment aimed at retaining HIV-positive women in care in Zimbabwe.